How to make chocolate candies : dipped, rolled, and filled chocolates, barks, fruits, fudge, and more - Collins, Bill, frey50 (North Adams, MA Storey Publishing, 2014)
Create your own homemade chocolate candies! With clear step-by-step instructions, Chef Bill Collins shows you exactly how to temper chocolate, work with thickeners, boil sugar, use piping bags, shape and fill molded chocolates, dip chocolates, and more. And he includes delicious, simple recipes for all kinds of rolled and filled chocolates, nut barks, chocolate-covered fruits, and fudge. Irresistible!
Includes index.
Keywords: Chocolate candy; Chocolate candy; Cookbooks